Dentists’ perspective on preference for direct restorative materials for different tooth cavities: A study from two colleges in Kathmandu, Nepal - Poudel, Keshav Raj; Gautam, Suman; Pokhrel, Prenit; Raghubanshi, Bijendra Raj; Shrestha, Amshuman; Raut, Binod (Journal of Kathmandu Medical College, 2014)
Background: Restoration of carious teeth is required to preserve anatomy, function and aesthetics of a tooth. Proper restoration of carious teeth is paramount for the prevention of progression of a dental caries so as to obviate the need for root canal treatment. Location, extent, type, duration and cost play the major roles for the selection of a dental filling material. Objective: This study was set to know the preference of dentists for the selection of filling materials for different tooth cavities. Methods: This was cross-sectional observational study carried out at Kantipur Dental College and KIST Medical College for a period of six months. Pre-structured questionnaires were distributed to the dentists who were in dental practice and collected questionnaires were analyzed for the results. Data were compiled, entered and analyzed using Microsoft Excel 2007 and Epi Info 2000. Yates corrected Chi square test was used wherever applicable and level of significance was set at <0.05. Results: Out of 65 questionnaires distributed to the dental practitioners, 57 (87.7%) questionnaires were returned. Composite was the material of choice as the restorative material for all kinds of tooth cavities except for class V for which glass ionomer cement was the main choice (52.6%). After composite, dental amalgam was second most preferred material for posterior tooth restorations. Order of preference for filling materials for posterior restorations were: composite (52.6%), dental amalgam (47.4%), miracle mix (68.3%; P<0.05) and glass ionomer cement (42.1%). Majority of practitioners (78.9%,P<0.05) opined that strength and durability of restorative material is the main guiding factor for the selection of the filling material for posterior tooth restorations. Additionally, dental amalgam had higher (68%, P< 0.05) patient satisfaction with respect to cost and longevity or durability and was associated with less tiring and time consuming procedure (84%; P<0.05) on dentists’ view. Conclusion: Majority of dentists opined that composite is the more preferred filling material for both anterior and posterior tooth restorations. For posterior tooth cavities (mainly for class I, II and VI) after composite, the order preference for filling materials was amalgam, miracle mix and glass ionomer cement. DOI: http://dx.doi.org/10.3126/jkmc.v3i2.11230 Journal of Kathmandu Medical College Vol. 3, No. 2, Issue 8, Apr.-Jun., 2014 Page: 72-77